Changes In Astigmatisma Before And After Pterygium Surgery At Undaan Eye Hospital, Surabaya - Eko Dian Hs; Agus Priyanto; Achmad Parjiko Adji Sanjaya (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
Pterygium is a common external ocular disease with a prevalence ranging between 0.7% and 33% globally. The disease is described as a wing-shaped, fibrovascular lesion that traverses the nasal or temporal limbs. This study aims to determine changes in astigmatism before and after pterygium surgery at the Undaan Eye Hospital in Surabaya. The population in this study were all pterygium sufferers who had changes in astigmatism before and after surgery at the Undaan Eye Hospital Polyclinic, Surabaya. The sample of 47 people was selected using probability sampling with the type "simple random sampling" or random sample. The instrument in this study used an observational sheet. The results of the study using the Mann-Whitney statistical test showed that the mean value before pterygium surgery was 3.89 and after pterygium surgery 1. 38. Through the Mann-Whitney test, it shows that there are changes in astigmatism before and after the pterygium surgery is carried out. Based on the significance value (p value), the value obtained is 0.000 < α (0.05), meaning that Ha is accepted or there is a change in astigmatism before and after pterygium surgery. The implication of this study is that pterygium surgery affects astigmatism changes.